The effect of psychological counseling program in improving the cognitive side of (hardness to flexibility) and learning some basic skills of basketball PreparationThe effect of psychological counseling program in improving the cognitive side of (hardness - Dr. Shatha Abdul-hafidh Ismaeil (physical education and sport sciences college for women/ Baghdad University, 2020)
OBJECTIVE: To identify the effect of psychological counseling program on improving the cognitive side from rigidity to elasticity . And the number of exercises (guidance - psychological) for the demands of adolescent learners of the game of basketball, the researcher used the experimental method; to answer the questions of the study, the scale consists of (56) paragraph, the researcher presented to a group of experts and specialists The five-point response scale (I strongly agree, agree, disagree and disagree, disagree, disagree). The grades are given (5 to very high) to 1-degree dissatisfaction. Palestine High School, the researcher concluded . The effectiveness of the guidance program in alleviating the stiffness and flexibility of the students of the Palestine Preparatory School and the vocabulary of the guidance program led to a positive increase from the hardness to flexibility than it was before the application